Robotic Fabrication in Architecture, Art and Design 2018 Foreword by Sigrid Brell-Çokcan and Johannes Braumann, Association for Robots in Architecture - Willmann, Jan; Block, Philippe; Hutter, Marco; Byrne, Kendra; Schork, Tim (Springer International Publishing : Imprint: Springer, 2019)
The book presents research from Rob/Arch 2018, the fourth international conference on robotic fabrication in architecture, art, and design. In capturing the myriad of scientific advances in robotics fabrication that are currently underway - such as collaborative design tools, computerised materials, adaptive sensing and actuation, advanced construction, on-site and cooperative robotics, machine-learning, human-machine interaction, large-scale fabrication and networked workflows, to name but a few - this compendium reveals how robotic fabrication is becoming a driver of scientific innovation, cross-disciplinary fertilization and creative capacity of an unprecedented kind.